1952
DOI: 10.1161/01.cir.6.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Electrocardiographic Changes during Exercise (Modified Double Two-Step Test)

Abstract: A method of recording electrocardiograms during the performance of a double two-step exercise test is described. Data

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

1959
1959
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…Although interpretation of results depends upon electrocardiographic changes, these have not been monitored routinely during exertion, even though a suitable technique was described 10 years ago. 3 The exercise stress varies with age, sex and body weight, but in terms of energy expenditure per unit of weight the underweight individual is stressed much more than the overweight person.…”
mentioning
confidence: 99%
“…Although interpretation of results depends upon electrocardiographic changes, these have not been monitored routinely during exertion, even though a suitable technique was described 10 years ago. 3 The exercise stress varies with age, sex and body weight, but in terms of energy expenditure per unit of weight the underweight individual is stressed much more than the overweight person.…”
mentioning
confidence: 99%
“…Similarly, Zack et al [9] presented a case report of normalization of T waves occurring with inflation of the balloon during coro nary angioplasty. Several studies have emphasized a pos sible link between normalization of inverted T waves and myocardial ischemia [1,2,7], Investigators have also used the occurrence of normalization of T waves as an indica tion of ischemia. Nadamanee et al [10] used normaliza tion of T waves as a criteria for ischemia in evaluating patients with silent ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…Soffer [1] and Bellet et al [2] were some of the first to mention that reversion of a previously inverted T wave to upright may be indicative of ischemia. Marin et al [3] used thallium-201 scintigraphy in patients with a high prevalence of coronary artery disease and found that nor malization was specific for the presence of coronary artery disease but not for ischemia.…”
Section: Introductionmentioning
confidence: 99%
“…A delay in HR recovery has been observed in patients with chronic heart failure Studies of the electrocardiogram during and after exercise (walking on a treadmill ergometer at standard speed and grade) in normal subjects have been performed for very long time [1,2].…”
Section: Introductionmentioning
confidence: 99%